1921 ANAYASASI’NIN 100. YILI:BİR İSTİSNAİ BAŞARI VE DRAMATİK BAŞARISIZLIK HİKÂYESİ - (:unkn) unknown (My University, 2021)
Yüzyıl önce olağanüstü yetkilerle toplanan Büyük Millet Meclisininçoğulcu, katılımcı, siyasi baskı ve yönlendirmelerden uzak bir şekildemüzakereci yöntemlerle yaptığı 1921 tarihli Teşkilat-ı Esasiye Kanunu,Osmanlı-Türk Anayasa geleneğinin dışında, iktidarın sınırlandırılması vedenetlenmesi, temel haklara yaklaşım, birey-devlet tasavvuru ve erklerbirliği gibi temel siyasal tercihleri ile güçlü bir adem-i merkeziyetçiliktercihiyle yerel yönetimleri egemenliğin kullanımına paydaş yapmasıbakımından istisnai bir anayasadır. Türkiye tarihinin yapımı ve kapsamıitibarıyla tek demokratik anayasasıdır. Bu nedenle Anayasa geleneğiniiki farklı anayasal gelenek olarak düşünmek ve “1921 Anayasası ve diğerAnayasalar” şeklinde bir okuma yapmak daha isabetlidir.Bağımsızlık savaşını yürüten Meclisin olağanüstü şartlarda çıkardığıbu Anayasa farklılıkların birlikteliğini ve mücadelenin meşruiyetinisağlama konusunda yine tek başarılı anayasadır. Bununla birlikte buAnayasa aynı zamanda en kısa ömürlü anayasa olarak tarihe geçmiştir.1922 sonlarından itibaren gücünü kaybeden Meclisle birlikte etkinliğinikaybetmeye başlayan Anayasa, Meclisin feshedilip yerine muhalefetsizbir tek parti meclisinin ikame edilmesiyle birlikte önce köklü değişikliklereuğratılmış; bir yıl geçmeden de yürürlükten kaldırılmıştır. Dolayısıylabir yandan olağanüstü bir başarı hikâyesi iken aynı zamanda dramatikbir başarısızlık hikâyesine dönüşmüştür. Bunun nedenleri ve günümüzeışık tutacak derslerinin analitik ve interdisipliner bir bakışla araştırılıportaya konması gerekmektedir.

The 1921 Constitution, which was deliberatively drafted in pluralist and participatory procedures free from political oppression and interferences a century ago by the Grand National Assembly gathered with extraordinary powers, is an exceptional constitution distinct from the Ottoman Turkish constitutional tradition thanks to its basic political preferences such as restriction and supervision of the government, approach adopted therein regarding human rights, the concept of individual and state, unity of powers, and recognition of local authorities as a shareholder in the exercise of sovereignty by adopting decentralization. It is the only democratic constitution in Turkey’s history in terms of its construction and scope. Hence, it is more appropriate to consider the constitutional tradition as two different traditions and to reclassify it as “the 1921 Constitution and other Constitutions”. This constitution, which was adopted under extraordinary conditions by a Parliament conducting the War of Independence, is also the only constitution that could ever accomplish the unity in diversity and in maintaining the legitimacy of the struggle. Besides, this constitution also went down in history as the one lived for the shortest time. The Constitution, which started to lose its effectiveness as the Parliament was losing power since late 1922, was subject to radical changes with the abolition of the Assembly and its replacement with a single-party assembly without opposition. It was subsequently abolished in a year. So, besides being a story of extraordinary success, it has also become the story of a dramatic failure. The underlying reasons of this experience and lessons that will shed light on today should be examined and put forward from an analytical and interdisciplinary perspective.
The 100th Anniversary of the Constitution of 1921: A Story of Exceptional Success and Dramatic Failure